2014
DOI: 10.1161/strokeaha.114.005116
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hyperbaric Oxygen Therapy Promotes Neurogenesis Through Reactive Oxygen Species/Hypoxia-Inducible Factor-1α/β-Catenin Pathway in Middle Cerebral Artery Occlusion Rats

Abstract: Background and Purpose Hyperbaric oxygen (HBO) has been reported to be neuroprotective and improved neurofunctional outcomes in acute stroke. However it is not clear if delayed HBO enhances endogenous neurogenesis and promotes neurofunctional recovery. The aim of this study is to evaluate the effects of delayed HBO therapy on neurogenesis and its potential mechanisms. Methods One hundred and eleven male Sprague-Dawley rats survived for 7 days from 2 hours of middle cerebral artery occlusion (MCAO) and reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…This is a radial effect of stroke that triggers neural repair. Free radicals generated in penumbra and in peri-infarct tissue are part of the stimulus for neurogenesis [20,21]; cytokines activate astrocytes, promote angiogenesis, and induce axonal sprouting [19,22,23]; and synchronized neuronal activity induces axonal sprouting and the formation of new connections (Fig. 1) [24].…”
Section: Radial Stroke: Triggers For Neural Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a radial effect of stroke that triggers neural repair. Free radicals generated in penumbra and in peri-infarct tissue are part of the stimulus for neurogenesis [20,21]; cytokines activate astrocytes, promote angiogenesis, and induce axonal sprouting [19,22,23]; and synchronized neuronal activity induces axonal sprouting and the formation of new connections (Fig. 1) [24].…”
Section: Radial Stroke: Triggers For Neural Repairmentioning
confidence: 99%
“…Free radicals also directly activate neural stem cells through induction of growth factor signaling pathways [20]. Through these systems, free radical generation after stroke is one of the signals of poststroke neurogenesis [21,44]. Immature neurons in the largest germinal matrix, the subventricular zone (SVZ), respond to the stroke, migrate to the area of damage, and may participate in Fig.…”
Section: Radial Stroke: Triggers For Neural Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Under hypoxic conditions, HIF-1α is capable of regulating anaerobic metabolism by inducing the expression of its target gene, and promoting angiogenesis and an increase of erythropoietin, which ensures that the hypoxic tissues and cells maintain at a certain oxygen concentration and tolerate the hypoxic environment (25,26). Previous studies have demonstrated that, when cerebral ischemia occurs, HIF-1α-induced gene expression may promote reperfusion of the ischemic penumbra area, thus improving glucose transport, which helps to mediate the ability of cells to tolerate hypoxia and has an important protective role for ischemic and hypoxic neurons (27,28). Following mild transient ischemia and hypoxia, HIF-1α expression levels are increased, which induces ischemic and hypoxic tolerance and demonstrates the neuroprotective effect of HIF-1α against ischemia and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The actual evidence for this concept is limited, though. In addition to some studies showing no effect on surrogate markers of ROS production in experimental cerebral ischemia [35,36], a recent study suggested that delayed HBO therapy had a beneficial effect after cerebral ischemia as it promoted production of reactive oxygen species [37].…”
Section: Discussionmentioning
confidence: 99%